2017
DOI: 10.1016/j.virusres.2016.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of cassava genotypes to infection by cassava mosaic geminiviruses

Abstract: HighlightsCassava genotypes respond differently to infection by cassava mosaic geminiviruses.Cassava mosaic disease resistant loci prompt recovery from systemic infection.CMD symptoms are directly correlated with contents of viral DNA and virus specific small RNAs.CMD infected plants abundantly accumulate 21–24 nt of virus specific small RNAs.VsRNAs heterogeneously map the entire virus genome in both polarities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 62 publications
3
36
0
Order By: Relevance
“…TME 7S is a CMD-susceptible version of TME 7 previously described by Kuria , et al [28]. Plants inoculated with MePSY2-VIGS developed visible chlorosis/bleaching on the challenged leaves and then subsequently on systemic leaves within 10–15 days after bombardment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TME 7S is a CMD-susceptible version of TME 7 previously described by Kuria , et al [28]. Plants inoculated with MePSY2-VIGS developed visible chlorosis/bleaching on the challenged leaves and then subsequently on systemic leaves within 10–15 days after bombardment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This difference was not entirely unexpected, because of the parallel history of two sets of ACMV clones: infectious partialtandem-dimer clones were made via restriction-digestion/ligation from sap-inoculated Nicotiana benthamiana plants whereas the monomersegment-unit clones were cloned with PCR from the same original cassava field sample (1). We expect these complete infectious clone sequences will be of great utility to the community, given that many follow-up publications (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Plots of Illumina read depth across the length of the four infectious clone plasmids. The region in each plasmid corresponding each virus segment partialtandem-dimer unit is indicated with a black line under each graph.…”
Section: Main Textmentioning
confidence: 99%
“…Consequently, the resistant cassava lines produced in breeding programs in Tanzania, Madagascar, IITA, and elsewhere in Africa have several important characteristics that are closely associated and are manifestations of the same basic virus resistance mechanism (Thresh et al, 1998). These include: (1) compared with existing local cultivars a lower proportion of plants become infected and the infected plants display less severe symptoms, (2) the virus is incompletely systemic, with symptoms being restricted to certain shoots or branches, and (3) resistant varieties contain lower concentrations of virus than do susceptible ones (Patil and Fauquet, 2015a; Kuria et al, 2016), as demonstrated serologically by Fargette et al (1996). Because of low viral titers and the incomplete systemic spread of virus in these resistant varieties, a substantial proportion of the cuttings collected from infected plants are free of virus, even if taken from plants that were infected as cuttings or were infected at an early stage of growth by whiteflies.…”
Section: Cmg Resistance Breedingmentioning
confidence: 99%
“…Recently, it was reported that CMD-susceptible cassava cultivars that displayed no recovery or showed a weak recovery, accumulate higher levels of viral small interfering RNAs (vsiRNAs) compared with genotypes that exhibited a strong recovery (Bengyella et al, 2015; Patil and Fauquet, 2015a; Kuria et al, 2016; Rogans et al, 2016). While these observations provide the first insights into small RNA (sRNA) profiles of CMD recovered and non-recovered phenotypes, important questions remain.…”
Section: Reversionmentioning
confidence: 99%